The genomic footprints of migration: how ancient DNA reveals our history of mobility - Matthew P. Williams; Christian D. Huber (Genome Biology)
Abstract Ancient DNA has emerged as a powerful tool for studying human migration through the detection of admixture signatures. Here, we present the theoretical principles and methodologies for admixture analysis, with an emphasis on f-statistics and qpAdm. We review case studies from the literature demonstrating how these methods uncover patterns of human mobility, and discuss challenges related to data quality, demographic complexity, and sample representativeness on admixture and migration inferences. Finally, we highlight promising advancements in admixture analysis and underscore the importance of integrating genetic, archaeological, and historical data to achieve a more interdisciplinary and nuanced reconstruction of human history.